CASE REPORT Broad Ligament Pregnancy - Farida Wagan, Rashida Akber (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2017)
A rare form of ectopic pregnancy can presented in broad ligament .diagnosis is often missed in these types of cases. Maternal mortality and morbidity is very high in these rare cases. Ween-countered broad ligament ectopic pregnancy with uneventful recovery.